Altenusin, a fungal metabolite, alleviates TGF-β1-induced EMT in renal proximal tubular cells and renal fibrosis in unilateral ureteral obstruction - Natechanok Thipboonchoo; Somsak Fongsupa; Sanya Sureram; Suliporn Sa-nguansak; Chatchai Kesornpun; Prasat Kittakoop; Sunhapas Soodvilai (Heliyon, 2024)
Renal fibrosis is a pathological feature of chronic kidney disease (CKD), progressing toward end-stage kidney disease (ESKD). The aim of this study is to investigate the therapeutic potential of altenusin, a farnesoid X receptor (FXR) agonist derived from fungi, on renal fibrosis. The effect of altenusin was determined (i) in vitro using the transforming growth factor β1 (TGF-β1)-induced epithelial to mesenchymal transition (EMT) of human renal proximal tubular cells and (ii) in vivo using mouse unilateral ureteral obstruction (UUO). The findings revealed that incubation of 10 ng/ml TGF-β1 promotes morphological change in RPTEC/TERT1 cells, a human renal proximal tubular cell line, from epithelial to fibroblast-like cells. TGF-β1 markedly increased EMT markers namely α-smooth muscle actin (α-SMA), fibronectin, and matrix metalloproteinase 9 (MMP-9), while decreased the epithelial marker E-cadherin. Co-incubation TGF-β1 with altenusin preserved the epithelial characteristics of the renal epithelial cells by antagonizing TGF-β/Smad signaling pathway, specifically a decreased phosphorylation of Smad2/3 with an increased level of Smad7. Interestingly, the antagonizing effect of altenusin does not require FXR activation. Moreover, altenusin could reverse TGF-β1-induced fibroblast-like cells to epithelial-like cells. Treatment on UUO mice with 30 mg/kg altenusin significantly reduced the expression of α-SMA, fibronectin, and collagen type 1A1 (COL1A1). The reduction in the renal fibrosis markers is correlated with the decreased phosphorylation of Smad2/3 levels but does not improve E-cadherin protein expression. Collectively, altenusin reduces EMT in human renal proximal tubular cells and renal fibrosis by antagonizing the TGF-β/Smad signaling pathway.